1995
DOI: 10.1177/014860719501900133
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chemically Defined Structured Lipid Emulsions on Reticuloendothelial System Function and Morphology of Liver and Lung in a Continuous Low‐Dose Endotoxin Rat Model

Abstract: The results of this study indicate that chemically defined structured lipids reduce fatty infiltration of the liver compared with a physical mixture of the same compounds in an animal model of metabolic stress. They were accompanied by a better function of the reticuloendothelial system and a lesser bacterial sequestration in the lungs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…To explain the importance of the structure in dietary TG, some researchers pointed out that the structural difference between fish oil and sea lion oil also affected the lipid metabolic function ( , ) . Some structured lipids have been known to modulate various immune functions ( ); thus, the structure of dietary TG-CLA deserves consideration. Therefore, even if there is no difference in the lymphatic absorption efficiency between TG- and FFA-CLA, the resulting structure of TG after the resynthesis in intestinal epithelial cells may have important and sequential effects on the immune function.…”
Section: Discussionmentioning
confidence: 99%
“…To explain the importance of the structure in dietary TG, some researchers pointed out that the structural difference between fish oil and sea lion oil also affected the lipid metabolic function ( , ) . Some structured lipids have been known to modulate various immune functions ( ); thus, the structure of dietary TG-CLA deserves consideration. Therefore, even if there is no difference in the lymphatic absorption efficiency between TG- and FFA-CLA, the resulting structure of TG after the resynthesis in intestinal epithelial cells may have important and sequential effects on the immune function.…”
Section: Discussionmentioning
confidence: 99%
“…In this aspect, our study supports a recent study in which no differences in energy expenditure or substrate oxidation were found in a crossover trial with 11 healthy volunteers who consumed three meals with modified fats containing octanoic acid and LCFA in the same proportions but in different sn-positions (structured MLM, randomized fats, and physically mixed fats) (24). Although structured lipids have, to date, not proven to reduce the postprandial lipid response or increase satiety in healthy adults compared with randomized fats with the same FA composition, structured lipids of MLM are important in the nutritional support of patients suffering from malabsorption (23,25,26). Changes in the chylomicron TAG M.W.…”
Section: Resultsmentioning
confidence: 99%